Efecto de la fertiirrigación en la nutrición del cultivo de palma aceitera (Elaeis guineensis. Jacq) - Gavilánez Lascano, Rodrigo Isaías (2024)
In the development of this research based on the “Effect of fertiirrigation on the nutrition of oil palm crops (Elaeis guineensis. Jacq).” in which the objective was set to describe the effects of fertiirrigation on the absorption of nutrients in oil palm cultivation, focused on growth and performance through bibliographic reviews. The methodology is determined to be based on a type of basic research, where it was developed under a descriptive-analytical approach, with a qualitative research design, in its development it determined, the importance of oil palm in Ecuador, the characteristics botany, reproductive characteristics, nutritional requirements of oil palm, water requirement in cultivation, the importance of different types of agricultural analysis in cultivation, and why do soil analysis for fertiirrigation. Regarding the results, Ammonium Nitrate, Potassium Nitrate, Monoammonium Phosphate, Potassium Sulfate are the main soluble fertilizers used in fertiirrigation for oil palm cultivation; With this technique, fertilizer doses can be adjusted according to the specific needs of plants at different stages of growth, allowing the use of resources to be optimized and productivity to be maximized. In conclusion, these soluble fertilizers were shown to provide important micronutrients and macronutrients such as nitrogen, phosphorus and potassium, which are essential for optimal palm growth.